Edge of dreaming [videorecording (DVD)] - Hardie, Amy (Lorber Films, 2010)
"Scottish filmmaker Amy Hardie built a career on making science documentaries, reflecting her staunchly rational mind. Then one evening she had a haunting dream of her horse dying, waking to discover that her beloved horse had passed away that same night. Shaken, she tried to pass it off as mere coincidence. But then she had another disturbing slumber, a nightmare where her deceased ex-husband predicts that she will die at age 48. After a foreboding doctor's visit, and with her 49th birthday mere months away, she starts to wonder about the explanatory power of dreams and their impact on her own mortality. In Edge of Dreaming, Amy looks for answers everywhere, from leading biologists Weissmann of and neuroscientists to the more spiritual solutions of a shaman. With the love and support of her family, Amy chronicles her quest to untangle the knots in her unconscious and the meaning of her destabilizing dreams"--www.kino.com.